Expected Utility and Continuity - Foldes, L. (Review of Economic Studies, 1972)
Journal Article Expected Utility and Continuity Get access Lucien Foldes Lucien Foldes London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 4, September 1972, Pages 407–421, https://doi.org/10.2307/2296509 Published: 01 September 1972